GDP Growth, Potential Output, and Output Gaps in Mexico - Faal, Ebrima (IMF Working Papers; Working Paper ;, 2005)
This paper analyzes the sources of Mexico's economic growth since the 1960s and compares various decompositions of historical growth into its trend and cyclical components. The role of the implied output gaps in the inflationary process is then assessed. Looking ahead, the paper presents medium-term paths for GDP based on alternative assumptions for productivity growth rates. The results indicate that the most important factor underlying the slowdown in output growth was a decline in trend total factor productivity growth. Economic policy reforms and the introduction of NAFTA may have raised trend productivity growth in recent years. Further increases in productivity growth would appear necessary, however, to raise medium-term growth.